Bilateral Internal Auditory Canal (IAC) Duplication with Congenital Sensorineural Hearing Loss (SNHL)-A Case Report - Nik Othman, Nik Adilah; Mohamad, Nur Saadah; Mohamad Jamali, Ahmad Aizuddin; Abdullah, Mohd Shafie; Md Daud, Mohd Khairi (IIUM Medical Journal Malaysia, 2021)
Duplication of the internal auditory canal is a rare entity. It can be unilateral or bilateral involvement and usually found during an investigation of sensorineural hearing loss or facial nerve palsy. We report this image finding in a child with Down syndrome with bilateral profound sensorineural hearing loss. There was no facial nerve palsy. We highlight the rarity of this image finding and the importance of imaging for detection of middle and inner ear abnormality in a case of congenital sensorineural hearing loss as it helps in decision making for the suitable treatment. Keywords: Duplicate IAC; Bilateral Duplicate IAC; sensorineural hearing loss; Down syndrome